2006
DOI: 10.1111/j.1467-7652.2006.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal characterization of polyhydroxybutyrate accumulation in sugarcane

Abstract: SummaryWe report here the results from a glasshouse trial of several transgenic sugarcane ( Saccharum spp. hybrids) lines accumulating the bacterial polyester polyhydroxybutyrate (PHB) in plastids. The aims of the trial were to characterize the spatio-temporal pattern of PHB accumulation at a whole-plant level, to identify factors limiting PHB production and to determine whether agronomic performance was affected adversely by PHB accumulation.Statistical analysis showed that a vertical PHB concentration gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(62 citation statements)
references
References 22 publications
(42 reference statements)
7
52
1
2
Order By: Relevance
“…The number of granules increased in line with the maturity of the leaves indicating accumulation of the PHB polymer throughout the developmental stage of the A. thaliana plant (Figures 5b to 5d). This result is in accordance with other studies which also indicated that the accumulation of PHB granule being the lowest in the youngest leaves and increasing with the leaf age (Purnell et al, 2007;Somleva et al, 2008;Petrasovits et al, 2012). The PHB fluorescence granules were abundantly distributed throughout the leaf of palisade chlorophyll rather than sponge mesophyll.…”
Section: Log Input Log Inputsupporting
confidence: 93%
See 2 more Smart Citations
“…The number of granules increased in line with the maturity of the leaves indicating accumulation of the PHB polymer throughout the developmental stage of the A. thaliana plant (Figures 5b to 5d). This result is in accordance with other studies which also indicated that the accumulation of PHB granule being the lowest in the youngest leaves and increasing with the leaf age (Purnell et al, 2007;Somleva et al, 2008;Petrasovits et al, 2012). The PHB fluorescence granules were abundantly distributed throughout the leaf of palisade chlorophyll rather than sponge mesophyll.…”
Section: Log Input Log Inputsupporting
confidence: 93%
“…The expression patterns of all the PHB genes were similar to findings from other studies (Purnell et al, 2007;Somleva et al, 2008;Parveez et al, 2015) where they found that in the PHB producing plants, the expression of phbC was the lowest among the three genes even though the genes were controlled by the same promoter.…”
Section: Transgene Expression Analysis By Reversetranscription-qpcrsupporting
confidence: 88%
See 1 more Smart Citation
“…Recombinant bacteria were originally used to produce PHB, but production costs were too high compared to production of synthetic plastics (Choi and Lee, 1999). As an alternative, researchers have attempted to produce PHB in transgenic plants including Arabidopsis thaliana (Poirier et al 1992;Bohmert et al 2000), Brassica napus (Houmiel et al 1999), corn (Poirier and Gruys, 2002), potato (Bohmert et al 2002), sugarcane Purnell et al 2007), andtobacco (Bohmert et al 2002;Lössl et al 2003;Arai et al 2004).…”
Section: Polyhydroxybutyratementioning
confidence: 99%
“…PHB synthesis in biomass crops of industrial interest such as switchgrass (Panicum virgatum; Somleva et al, 2008), sugarcane (Saccharum spp. hybrids; Petrasovits et al, 2007;Purnell et al, 2007), and corn stover (leaves and stock of Zea mays; Poirier and Gruys, 2002) have also been reported. Further work, however, is needed to increase levels in these crops for commercial purposes.…”
mentioning
confidence: 99%